Dança e adaptabilidade: processos de comunicação entre corpo e ambiente - Liparotti, Thábata Marques (2013)
The goal of this essay is to identify the communication processes between body and environment that enable the adaptability seen during the creational process of A(da)pto‟ ( A(da)pt‟, in a literal translation), having this artistic movement as study subject. The specific goals are to identify the states (body and environment) and the adjustments in the movement; to inventory the alterations occurred from the exchange of information between body and environment that may be indicators of adaptability; to discuss possibilities of perception and self-organization of the bodies. Therefore, this essay focus on questioning if communication, seen as the exchange of information between body and environment, is the mean for adaptability to happen and if, as a consequence, we may be able to think communication as the key‟ to adaptability. The hypothesis built suggests that by the possibility of exchanging information the organisms rise their survival rate. Thereby, once capturing information from the world coherently and efficiently, solutions of interaction between body and environment are created. Communication would then allow the adaptability process to happen. As a method, we have chosen for this essay a qualitative approach of exploratory character. Therefore, the work of dance A(da)pto‟, performed in a mountain chain in Marumbi-PR, has been used as empirical exemplification to validate this hypothesis. The communication processes involved are identified and analyzed through reports which contain a list of particularities of each investigation day. To capture tacit aspects, videos of the experiment have been used. The theoretical reference taken includes the following authors: Vieira (2006; 2007; 2008) to approach the concepts of Umwelt, systemic parameters and complexity; Moran (2010) to discuss human adaptability; Santaella (1992; 1993; 2008; 2010) about perception and communication, and Katz and Greiner (2005) with their body-media theory to the understanding of the body and the dance. In this essay, two phases of communication processes between body and environment that enable adaptability have been identified. The first as an exchange of information between body and environment; the second, as alterations occurred to the body and the way it creates a communication code of adaptability to the audience. It has been noticed that these phases, though distinct, have sometimes occurred simultaneously, once the body starts, at the same time, to build and structure ideas whereas it continues to reorganize itself to the environmental stimuli. From the analysis of these phases, we come to conclude that the adaptability in Marumbi refers to the possibility of self-organization when facing the mode information to dilate the Umwelt. Thus, body and environment keep a flow of continuous adjustments, not attached to movement patterns. Adaptability, therefore, happens through communication, which may be considered the key‟ to adaptability in search of the human species prevalence